2022
DOI: 10.1002/cssc.202102504
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Electrochemical Reduction of 5‐Hydroxymethylfurfural at High Current Densities

Abstract: The electrocatalytic reduction of 5-hydroxymethylfurfural (HMF) is highly selective to 2,5-bishydroxymethylfuran (BHMF) at pH = 9.2, diluted HMF solutions, and low current densities. In this work, the electrochemical reduction of 0.05 m HMF solutions was investigated in the 5-50 mA cm À 2 current density range over an AgCu foam electrocatalyst. The selectivity towards the formation of BHMF or the dimerization depended on the current density, likely due to differences in the electrode potential, and on the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Sanghez de Luna et al reportedly applied high current density on highly active Cu foam-based Ag/Cu GD 55 in a concentrated HMF solution (50 mM). 77 It was found that conduction at a current density 40 to 50 mA cm −2 allowed a "trade-off" between HMF hydrogenation and the HER and exhibited 85% DHMF selectivity and significant production of 0.567 mmol cm −2 . In this reaction to obtain high DHMF production, the applied potential for current density needs to be in the HER window, in which HMF reduction is favored over H 2 production on Ag/Cu GD, and there is sufficient H* on the electrode to prevent HMF dimerization and to ensure HMF hydrogenation is more competitive.…”
Section: Electrolyte Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanghez de Luna et al reportedly applied high current density on highly active Cu foam-based Ag/Cu GD 55 in a concentrated HMF solution (50 mM). 77 It was found that conduction at a current density 40 to 50 mA cm −2 allowed a "trade-off" between HMF hydrogenation and the HER and exhibited 85% DHMF selectivity and significant production of 0.567 mmol cm −2 . In this reaction to obtain high DHMF production, the applied potential for current density needs to be in the HER window, in which HMF reduction is favored over H 2 production on Ag/Cu GD, and there is sufficient H* on the electrode to prevent HMF dimerization and to ensure HMF hydrogenation is more competitive.…”
Section: Electrolyte Compositionmentioning
confidence: 99%
“…Current density changes the mechanism and product selectivity because of product distribution caused via the concentration overpotential. Sanghez de Luna et al reportedly applied high current density on highly active Cu foam-based Ag/Cu GD in a concentrated HMF solution (50 mM) . It was found that conduction at a current density 40 to 50 mA cm –2 allowed a “trade-off” between HMF hydrogenation and the HER and exhibited 85% DHMF selectivity and significant production of 0.567 mmol cm –2 .…”
Section: Additional Factors For Hrrmentioning
confidence: 99%
“…For the construction of double sites, the combination of a precious metal (Ag or Ru) with Cu is found to be a suitable candidate for the hydrogenation of HMF. [83][84][85] In the macro aspect, the introduction of Cu directly leads to the dispersion of noble metal sites and the improvement of the electrocatalytic activity. In the micro aspect, the electron transfer from the catalyst to HMF increases, resulting in the decrease in energy barrier and Gibbs free energy of the HMF hydrogenation reaction relative to the direct utilization of Ag, as certified by density functional theory (DFT) calculations.…”
Section: Electrocatalytic Reduction Of Biomass Feedstocksmentioning
confidence: 99%
“…Very recently, this 3D nanostructured Ag/Cu ED was further utilized in operation at high current densities (40-50 mA cm −2 ), which enabled a trade-off between the activation of HMF and H 2 O with remarkable selectivity (85%) and productivity (0.567 mmol cm −2 h −1 ). 85 The smaller size of AgCu nanoalloys (Ag 1 Cu 1 /PA, Ag 3 Cu 1 / PA, and Ag 1 Cu 3 /PA) loading on pyrolyzed sodium alginate (PA) enabled the faster kinetic of ECH. 86 With an average size of 7.4 nm, Ag 1 Cu 1 /PA performed the optimal selectivity of 94% for BHMF, with a favorable ECH over HER in a 0.05 M borate buffer solution over a wide potential ranging from −0.26 to −1.12 V vs. RHE.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…Very recently, this 3D nanostructured Ag/Cu ED was further utilized in operation at high current densities (40–50 mA cm −2 ), which enabled a trade-off between the activation of HMF and H 2 O with remarkable selectivity (85%) and productivity (0.567 mmol cm −2 h −1 ). 85…”
Section: Electrochemical Hydrogenation Of Furansmentioning
confidence: 99%